A 160mpa grade high formability economic if steel and a method of making the same
Patent Information
- Application Number
- CN202611196877.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0012]本发明的目的在于克服现有技术存在的160MPa强度级别IF钢生产中,因单一强化体系及热轧、退火工艺缺乏精准调控导致细小析出物钉扎晶界阻碍γ织构形成,从而造成r值显著下降、延伸率降低、难以兼顾较高强度与优异深冲成形性的上述缺陷,提供一种160MPa级高成形性经济型IF钢及其制备方法,通过成分与工艺的协同创新,生产的IF钢实现强度与成形性的协同提升,在低成本条件下实现了屈服强度为145~170MPa;抗拉强度为305~335MPa;塑性应变比r值≥2.9;延伸率A80为47%~51%;加工硬化指数n值为0.24~0.28,可广泛应用于汽车内板、结构件及高性能家电面板等领域
本发明突破传统IF钢成分设计思路,采用Ti-V-Ca-B经济型复合微合金化体系,在保证基体纯净度的同时降低合金成本;提出V/Ti和Ca/S双比例控制参数,优化复合析出与硫化物球化,优化其深冲性能。针对V(C,N)低温析出特性,采用690~720℃中温卷取工艺,促使V(C,N)弥散析出、TiC尺寸适中,获得析出强化效果,同时保留足够形变储能;同时匹配设计的罩式退火工艺,避免了V(C,N)回溶,将晶粒细化,缩短了退火周期且降低能耗。通过上述成分与工艺的系统性协同,本发明在低成本条件下实现了屈服强度为145~170MPa、抗拉强度为305~335MPa、塑性应变比r值≥2.9、延伸率A80为47%~51%、加工硬化指数n值为0.24~0.28的优异性能组合,可广泛应用于汽车内板、结构件及高性能家电面板等领域。
Smart Images

Figure CN122979748A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ultra-low carbon IF steel manufacturing technology, and more specifically, to a 160MPa grade high formability economic IF steel and its preparation method. Background Technology
[0002] Interstitial-free (IF) steel is a clean ferritic steel produced by adding strong carbonitride-forming elements such as Ti or Nb to ultra-low carbon steel. This completely fixes the interstitial atoms (C and N) in the steel into carbonitride compounds, resulting in a steel free of interstitial atoms. IF steel possesses extremely excellent deep-drawing properties, high elongation, high plastic strain ratio (r value), high work hardening index (n value), and no aging properties, making it the leading material in deep-drawing applications such as automotive exterior panels, complex structural parts, and high-end appliance panels.
[0003] With the increasing demands for lightweighting and performance in the automotive industry, the performance requirements of IF steel for different components are becoming increasingly diverse: outer body panels prioritize extreme deep-drawing performance (yield strength ≤ 130 MPa), while inner panels, structural components, and some household appliance parts require higher strength (yield strength approximately 160 MPa) while maintaining good formability to meet the requirements for dent resistance and component stiffness. However, existing IF steel products generally face the technical challenge of balancing strength and formability when achieving a strength level of 160 MPa. While adding solid solution strengthening elements such as P, Mn, and Si, or increasing the Ti content for precipitation strengthening can improve strength and achieve a yield strength above 160 MPa, it leads to a significant decrease in the r-value (usually below 2.5), reduced elongation, and deteriorated deep-drawing performance, making it difficult to meet the processing requirements of complex formed parts. Existing technologies struggle to achieve both a high r-value (≥2.9) and excellent elongation at the 160MPa strength level, primarily due to: the inhibitory effect of a single solid solution strengthening or precipitation strengthening system on texture development; improper control of coiling temperature and precipitate size during hot rolling, leading to fine precipitates pinning grain boundaries and hindering γ-texture formation; and the lack of precise control over the annealing process for medium strength levels, making it impossible to obtain recrystallized structures while retaining a sufficient proportion of favorable textures.
[0004] Although there are many publicly available patents and documents on IF steel, most alloy designs employ single microalloying or simple composite microalloying, resulting in a contradictory effect between solid solution strengthening elements and high formability.
[0005] Chinese patent CN118703877A discloses an ultra-deep drawing IF steel and its preparation method. The composition is: C: 0.0015%~0.003%, Si: ≤0.05%, Mn: ≤0.4%, P: ≤0.025%, S: ≤0.025%, Al: 0.02%~0.1%, Ti: 0.02%~0.10%, Nb: 0.015%~0.025%, N ≤0.005%, with the balance being Fe and unavoidable impurities. This patent has an r-value of only 1.98~2.23, an elongation of only 34%~37%, and a relatively low strength grade.
[0006] Chinese patent CN113802062A discloses a B-microalloyed high-elongation, low-yield-strength IF steel. The composition is: C: ≤0.0020%, Si: ≤0.010%, Mn: ≤0.08%, P ≤0.008%, S: ≤0.006%, N ≤0.0020%, Als: 0.015%~0.045%, Ti: 0.040%~0.054%, B: 0.0008%~0.0020%, with the balance being Fe and unavoidable impurities. This patent reduces the interstitial atom content by adding trace amounts of B to combine with N and form BN. However, this patent still mainly relies on Ti to fix C and N, employing a relatively simple Ti microalloying treatment, which has significant limitations in texture control; the r value can only reach 2.65-2.85.
[0007] Chinese patent CN119776727A discloses a low-cost 320MPa grade hot-dip galvanized IF steel for automotive sheet metal and its preparation method. The composition is C: ≤0.003%, Si: ≤0.035%, Mn: 0.1%~0.3%, P: ≤0.02%, S: ≤0.015%, Ti: 0.03%~0.08%, B: 0.0001%~0.0008%, with the balance being Fe and unavoidable impurities. This patent has an r-value of only ≥2.0 and an elongation of only ≥37%, significantly insufficient deep-drawing performance, failing to meet the requirements of complex forming parts for high r-values (≥2.8). Furthermore, this patent employs a continuous annealing process.
[0008] Chinese patent CN118147537A discloses a high yield strength ratio IF steel with a yield strength of 180MPa and its production method. The composition is: C: ≤0.004%, Si: 0.11%~0.15%, Mn: 0.30%~0.40%, Als: 0.025%~0.050%, P: 0.041%~0.055%, S: ≤0.015%, N: ≤0.004%, Ti: 0.05%~0.07%, B: 0.0004%~0.0012%, with the balance being Fe and unavoidable impurities. This patent uses only a relatively simple micro-Ti treatment in its composition design, and the C and N content is relatively high, with an r-value of only 2.60-2.95. Furthermore, the yield strength is too high (≥180MPa), failing to meet the higher formability requirements of the 160MPa level. The patent also employs a continuous annealing process.
[0009] Chinese patent CN115478143A discloses a method for near-net-shape rolling of IF ferrite steel using an ultra-short process. The composition is: C: 0.0001%~0.005%, Si: 0.001%~0.02%, Mn: 0.01%~0.20%, P: ≤0.02%, S: ≤0.005%, N: ≤0.005%, Als: <0.001%, Ca: ≤0.0050%, Nb: 0.02%~0.08%, total oxygen [O]: 0.007%~0.020%, with the remainder being Fe and other unavoidable impurities. The patent's composition design allows for relatively broad control of the solid solution strengthening elements C, Si, Mn, and P. The hot rolling process employs a two-stage rolling process of austenite + ferrite. Furthermore, the patent lacks a subsequent cold rolling annealing process, resulting in poor overall performance.
[0010] Chinese patent CN117551938A discloses a high-strength IF steel hot-dip galvanized sheet and its preparation method. The composition is: C: 0.003%~0.012%, Mn: 0.3%~1.0%, Si: ≤0.05%, P: ≤0.03%, S: ≤0.005%, Als: 0.02%~0.07%, N: ≤0.003%, B: 0.0003%~0.0008%, Ti: 0.02%~0.09%, with the remainder being Fe and other unavoidable impurities. This patent's composition design features relatively wide control over the content of solid solution strengthening elements C, Si, Mn, and P, with relatively high addition levels. High strength (yield strength ≥230MPa) is achieved through TiC precipitation strengthening. However, this scheme sacrifices deep-drawing performance for strength, with an r-value of only 1.85-2.02. Furthermore, this patent employs a continuous annealing process.
[0011] Chinese patent CN120700406A discloses a low-carbon emission, high-performance IF steel plate and its preparation method. The composition is: C: ≤0.0030%, S: ≤0.0060%, Si: ≤0.030%, Mn: ≤0.2%, N: 0.0030%~0.006%, Al: 0.060%~0.12%, Ti: 0.030%~0.080%, Nb: 0.0015%~0.030%, B: ≤0.0008%, Cu: ≤0.12%, Sn: ≤0.01%, Cr: ≤0.15%, Ni: ≤0.08%, La+Se: 0.001%~0.02%. This patent has a relatively high yield strength and an r-value of only ≥2.2, indicating a poor match between strength and formability. It prioritizes low carbon emissions over deep-drawing performance. The hot rolling process uses ferritic rolling, and the patent employs a continuous annealing process. Summary of the Invention
[0012] The purpose of this invention is to overcome the shortcomings of existing technologies in the production of 160MPa strength-grade IF steel. These shortcomings stem from a single strengthening system and a lack of precise control over hot rolling and annealing processes, leading to fine precipitates pinning grain boundaries and hindering the formation of γ-texture. This results in a significant decrease in the r-value, reduced elongation, and an inability to simultaneously achieve high strength and excellent deep-drawing formability. This invention provides a 160MPa-grade high-formability, economical IF steel and its preparation method. Through synergistic innovation in composition and process, the produced IF steel achieves a synergistic improvement in strength and formability, achieving a yield strength of 145~170MPa, a tensile strength of 305~335MPa, a plastic strain ratio r-value ≥2.9, and an elongation A at low cost. 80 The hardening rate is 47%~51%; the work hardening index n value is 0.24~0.28, which can be widely used in automotive interior panels, structural parts and high-performance home appliance panels.
[0013] To achieve the above objectives, the technical solution of the present invention is as follows: A 160MPa grade high formability economical IF steel comprises the following components by weight percentage: C≤0.0020%, Si≤0.010%, Mn: 0.08%~0.12%, P: 0.012%~0.020%, S≤0.006%, Als: 0.020%~0.040%, Ti: 0.035%~0.055%, V: 0.008%~0.014%, B: 0.0004%~0.0008%, Ca: 0.001%~0.003%, N≤0.0025%, with the balance being Fe and unavoidable impurities.
[0014] This invention also discloses a method for preparing the 160MPa grade high formability economical IF steel as described above, including smelting, continuous casting, hot rolling, pickling, cold rolling, degreasing, bell-type annealing, and finishing; the preparation method includes the following steps: In the hot rolling process, the slab is directly fed into a walking beam furnace for heating. The slab heating temperature is 1160~1180℃; the holding time is ≥160min; the roughing rolling temperature is 1060~1100℃, and the cumulative reduction rate is 70%~85%; the finishing rolling temperature is 900~930℃; the finishing rolling cumulative reduction rate is 85%~95%; laminar flow cooling is used after rolling, with a cooling rate of 30~50℃ / s; and the coiling temperature is 690~720℃. In the hood-type annealing, a full hydrogen protective atmosphere is used, and the temperature is raised to 400-500℃ at a heating rate of 200-300℃ / h, then raised to 650-670℃ at a heating rate of 50-70℃ / h, then raised to 700-720℃ at a heating rate of 30-40℃ / h, and held at this temperature range for 6-8h. After that, the temperature is slowly cooled to 450-500℃ at a cooling rate of 25-35℃ / h, and finally slowly cooled to room temperature with the hood on.
[0015] Implementing the embodiments of the present invention will have the following beneficial effects: This invention breaks through the traditional design concept of IF steel composition, adopting an economical Ti-V-Ca-B composite microalloying system to reduce alloy costs while ensuring matrix purity. It proposes dual-ratio control parameters for V / Ti and Ca / S to optimize composite precipitation and sulfide spheroidization, thereby improving deep-drawing performance. Targeting the low-temperature precipitation characteristics of V(C,N), a medium-temperature coiling process at 690~720℃ is used to promote dispersed precipitation of V(C,N) and moderate TiC size, achieving precipitation strengthening while retaining sufficient deformation energy. Simultaneously, a designed bell-type annealing process is used to avoid V(C,N) re-dissolution, refine grains, shorten the annealing cycle, and reduce energy consumption. Through the systematic synergy of the above composition and process, this invention achieves a yield strength of 145~170MPa, a tensile strength of 305~335MPa, a plastic strain ratio r value ≥2.9, and an elongation A under low-cost conditions. 80 With an excellent performance combination of 47%~51% and a work hardening index n value of 0.24~0.28, it can be widely used in automotive interior panels, structural components, and high-performance home appliance panels.
[0016] Compared with the prior art, the present invention has the following advantages: 1) This invention breaks through the traditional strengthening approach of IF steel by adopting an economical Ti-V-Ca-B composite microalloying system. It reduces costs while ensuring performance, significantly enhancing the product's market competitiveness.
[0017] 2) This invention proposes control parameters for V / Ti and Ca / S ratios. V / Ti = 0.15~0.35 achieves the optimal balance between precipitation strengthening and γ-texture development; Ca / S = 0.5~2.0 significantly improves anisotropy. Simultaneously, by combining Ti / (C+N) = 12~18 and Als / N = 15~20, a quantitative correlation between composition, microstructure, and properties is established in a low-cost system, ensuring stable and controllable performance.
[0018] 3) This invention innovatively employs a medium-temperature coiling process to address the low-temperature precipitation characteristics of V(C,N), achieving precise synergy with the Ti-V composite microalloying composition. The medium-temperature coiling promotes the dispersed precipitation of V(C,N) in the ferrite region and ensures moderate TiC size, resulting in precipitation strengthening. Simultaneously, it retains sufficient deformation energy storage to drive the development of subsequent annealing γ-texture.
[0019] 4) The present invention adopts a two-stage annealing process with moderate heating and moderate holding. This process avoids the re-dissolution of V(C,N) precipitates, retains the precipitation strengthening effect, and obtains fine grain strengthening effect. At the same time, the annealing cycle is shortened and energy consumption is reduced, achieving a balance between high performance and high efficiency. Attached Figure Description
[0020] Figure 1 The image shows the metallographic structure of the 160MPa grade high formability economic IF steel of Example 1 of the present invention. Detailed Implementation
[0021] The present invention will be further described below with reference to specific embodiments, but this does not limit the present invention in any way.
[0022] This invention discloses a 160MPa grade high formability economical IF steel, comprising the following components by weight percentage: C≤0.0020%, Si≤0.010%, Mn: 0.08%~0.12%, P: 0.012%~0.020%, S≤0.006%, Als: 0.020%~0.040%, Ti: 0.035%~0.055%, V: 0.008%~0.014%, B: 0.0004%~0.0008%, Ca: 0.001%~0.003%, N≤0.0025%, with the balance being Fe and unavoidable impurities.
[0023] In one specific embodiment, the mass percentage ratio of the chemical composition of C, Ti and N in IF steel conforms to: Ti / (C+N)=12~18.
[0024] In one specific embodiment, the mass percentage ratio of V and Ti in the IF steel is V / Ti = 0.15~0.35.
[0025] In one specific embodiment, the mass percentage ratio of Ca and S in the IF steel conforms to the following: Ca / S = 0.5~2.0.
[0026] In one specific embodiment, the mass percentage ratio of Als and N in the IF steel conforms to the following: Als / N = 15~20.
[0027] The specific reasons for limiting the amounts of each chemical element in steel plates are detailed below: C and N are the most important interstitial atoms in IF steel. Their content should be reduced as much as possible. Solid solution of C and N is the main factor that increases yield strength, worsens r value, reduces elongation, and causes strain aging. However, if the content is too low, it will lead to increased processing costs. Therefore, C≤0.0020% and N≤0.0025%.
[0028] Si is a strong solid solution strengthening element that can significantly improve strength but reduce plasticity. Its content must be controlled within a suitable range to avoid increasing yield strength while ensuring deoxidation effect and surface quality; therefore, Si ≤ 0.010%.
[0029] Mn: Also a solid solution strengthening element, it increases strength by causing lattice distortion through solid solution, hindering dislocation movement. Simultaneously, Mn combines with S to form MnS, preventing hot brittleness. However, excessively high Mn content will decrease the r-value and increase cost. Therefore, the Mn content ranges from 0.08% to 0.12%.
[0030] Phosphorus (P) is a highly efficient solid solution strengthening element with high solubility in ferrite. Each 0.01% P increases the yield strength by approximately 5-6 MPa. However, P tends to segregate at grain boundaries, reducing grain boundary bonding and leading to secondary processing brittleness (cold brittleness). Therefore, this design controls P within the range of 0.012% to 0.020%.
[0031] S is an unavoidable impurity element in steel, and S combines with Mn to form elongated MnS. These elongated MnS particles extend along the rolling direction during rolling, severely disrupting anisotropy and reducing the r-value and elongation. Therefore, this design controls S at a low level (≤0.006%).
[0032] Als (Al₂S) is a strong deoxidizer that can reduce dissolved oxygen in steel and prevent oxide inclusions. Simultaneously, Al combines with N to form AlN. This design controls Als at 0.020%~0.040%, combined with an Als / N ratio of 15~20, to ensure that AlN preferentially precipitates and coarsens during the hot rolling stage, preventing it from pinning grain boundaries in a fine, dispersed form during annealing and eliminating its adverse effects on γ-texture development.
[0033] Ti is the most effective element for fixing C and N. Ti has a strong bonding force with C and N, forming TiC and TiN to fix interstitial atoms. In this design, the Ti content is 0.035%~0.055%, combined with a Ti / (C+N) ratio of 12~18 to ensure complete fixing of C and N, while maintaining an appropriate excess of Ti to promote the development of recrystallization texture. Too little excess Ti results in incomplete fixing, while too much leads to the formation of fine, dispersed TiC secondary precipitation, excessive pinning of grain boundaries, hindering the development of γ-texture, and also increasing the recrystallization temperature, making annealing more difficult, and increasing alloy cost.
[0034] V: is an economical microalloying element that forms V(C,N) precipitates with C and N. In this design, the V content is 0.008%~0.014%, controlled by a V / Ti ratio of 0.15~0.35. If the content is too low, sufficient precipitation strengthening cannot be guaranteed; if it is too high, too much V(C,N) will precipitate. If the V(C,N) is too fine, it will strengthen grain boundary pinning, which is not conducive to the development of γ texture and will also increase the cost of the alloy.
[0035] B: B has a small atomic radius and a strong tendency to aggregate at grain boundaries. It preferentially occupies grain boundary positions to form Fe-B or Fe-BP composite phases, which prevents harmful elements such as P from aggregating at grain boundaries and significantly improves the brittleness of secondary processing. However, if the content is too high, it forms FeB or Fe2B brittle phases, which will reduce toughness and elongation. Therefore, its suitable range is 0.0004%~0.0008%.
[0036] Ca (Ca) has a stronger affinity for sulfur than Mn (Mn), preferentially reacting with S to form high-melting-point spherical CaS, transforming harmful long MnS into spherical CaS, significantly improving anisotropy and increasing the r-value. Simultaneously, Ca can modify oxides, improving the cleanliness of molten steel. The optimal Ca / S ratio is controlled between 0.5 and 2.0. Too low a content results in incomplete spheroidization of sulfides, leaving residual long MnS; too high a content leads to the formation of large-sized CaO or CaS inclusions, which can become crack initiation sites. Therefore, the optimal range is 0.001% to 0.003%.
[0037] In one specific embodiment, the IF steel has a yield strength of 145~170MPa; a tensile strength of 305~335MPa; a plastic strain ratio r value ≥2.9; and an elongation A. 80 The percentage is 47% to 51%; the work hardening index (n) is 0.24 to 0.28.
[0038] This invention also discloses a method for preparing the 160MPa grade high formability economical IF steel as described above, including smelting, continuous casting, hot rolling, pickling, cold rolling, degreasing, bell-type annealing, and finishing; the preparation method includes the following steps: S1. In the smelting process, this includes hot metal pretreatment, top-and-bottom blowing converter, LF refining, and RH vacuum refining. In hot metal pretreatment, the hot metal undergoes desiliconization, desulfurization, and dephosphorization treatments. In the top-and-bottom blowing converter, the final carbon concentration is controlled to be ≤0.025%, and the final oxygen concentration is 400~500ppm. During tapping, aluminum particles are added for pre-deoxidation, and a sliding plate is used to control the slag amount, with the slag thickness controlled to ≤40mm and the slag amount consistently controlled within 60mm. The tapping temperature is controlled at 1660~1680℃. In LF refining, high-basicity reducing slag (CaO / SiO2≥5) is used. Deep desulfurization is carried out, with S ≤ 0.006% and refining time of 35~45 min. The temperature of molten steel is precisely controlled to 1610~1630℃. In RH vacuum refining, oxygen blowing is used for forced decarburization under high vacuum (≤60Pa), with C ≤ 0.0020% and [O] ≤ 0.0025%. Then, Ti-Fe, V-Fe, B-Fe and other alloy raw materials are added in sequence for alloying. At the end of alloying, Fe-Ca wire is added for calcium treatment to modify the long strip MnS into spherical CaS. After calcium treatment, the mixture is circulated for 3~5 min to promote the floating of inclusions.
[0039] S2. In continuous casting, a combination of technologies including full-process protective casting, low superheat, electromagnetic stirring, and dynamic light pressure is employed to ensure high-purity, defect-free billets. The tundish features a low-carbon working layer design with a capacity of ≥60 tons, and argon gas is used for full-process sealing protection from the ladle to the tundish and from the tundish to the crystallizer. The casting superheat is 20~30℃, which promotes the formation of equiaxed crystals and refines the as-cast microstructure. A combination of electromagnetic stirring in the crystallizer and at the end of the casting process is used to uniformly distribute the composition and reduce central segregation. A dynamic light pressure of 2~5mm is applied at the end of the billet solidification to compensate for solidification shrinkage and eliminate central porosity. A special protective slag for ultra-low carbon steel is used in conjunction with a weak cooling secondary cooling process to avoid carbon increase and surface cracks. The casting speed is 1.0~1.2m / min to obtain the billet.
[0040] In one specific embodiment, the non-metallic inclusions of types A, B, C, and D in the billet are ≤ grade 1.0; the inclusions in the billet are spherical and uniformly distributed; and the thickness of the billet is 210~230mm.
[0041] S3. In hot rolling, a process route of medium-temperature heating + austenitic zone rolling + medium-temperature coiling is adopted. The slab is directly hot-charged into a walking beam furnace for heating. The slab heating temperature is 1160~1180℃. At this heating temperature, some V precipitation strengthening can be retained, while avoiding austenite grain coarsening, refining the original grains, and reducing energy consumption. The holding time is ≥160min to ensure uniform slab temperature, allowing AlN to coarsen sufficiently, while avoiding excessive holding time that could lead to grain growth. The roughing and finishing rolling temperature is 1060~1100℃, and the cumulative reduction rate is 7%. The austenite reduction rate is 0%~85% to ensure sufficient dynamic recrystallization of austenite and obtain a uniform microstructure; the finishing rolling temperature is 900~930℃, and the finishing rolling is completed in the fully austenitic single-phase region to avoid entering the two-phase region and causing mixed crystals; the lower finishing rolling temperature can refine the austenite grains, increase the nucleation points of ferrite after phase transformation, and refine the final microstructure; at the same time, it creates conditions for subsequent medium-temperature coiling; the cumulative reduction rate of finishing rolling is 85%~95% to refine the austenite grains; laminar flow cooling is adopted after rolling, and the cooling rate is 30~50℃ / s; the coiling temperature is in the medium-temperature range of 690~720℃. This invention enables the V(C,N) precipitates to fully disperse and precipitate during cooling at a medium-temperature coiling temperature of 690~720℃, resulting in significant precipitation strengthening. If the coiling temperature is higher than 720℃, the V(C,N) precipitation coarsens, and the strengthening effect is greatly reduced; if the temperature is lower than 690℃, precipitation is insufficient, and some V remains in solid solution, weakening the strengthening effect. Simultaneously, TiC partial precipitation occurs at a suitable size, contributing to precipitation strengthening without excessively pinning grain boundaries. The entire hot rolling process is equipped with high-pressure descaling, hydraulic AGC thickness control, roll shape control, and edge heaters to ensure strip surface quality, thickness accuracy, and temperature uniformity, ultimately yielding a high-quality hot-rolled coil with uniform microstructure and spheroidized inclusions.
[0042] In one specific embodiment, the thickness of the hot-rolled raw material is 2.5~3.0 mm.
[0043] In S4, pickling and cold rolling, a combined pickling and rolling unit is used for continuous production. Hydrochloric acid pickling removes the iron oxide scale from the surface of the hot-rolled coil, ensuring surface cleanliness and providing high-quality raw materials for cold rolling. The total reduction rate of cold rolling is 80%~90%. The ultra-high reduction rate stores high-density dislocations and deformation bands in the strip matrix, providing sufficient driving energy for the nucleation of γ-fiber texture ({111} surface) during the subsequent bell-type annealing process. The cold rolling process uses a hydraulic AGC thickness control system to ensure thickness accuracy and is equipped with bending rolls and shifting roll devices to control the strip shape.
[0044] S5. In the bell-type annealing, a full hydrogen protective atmosphere is used. The temperature is raised to 400-500℃ at a heating rate of 200-300℃ / h, without holding in this temperature range. Then, the temperature is raised to 650-670℃ at a heating rate of 50-70℃ / h, and then raised to 700-720℃ at a heating rate of 30-40℃ / h. The temperature is held in this temperature range for 6-8 hours. After that, the temperature is slowly cooled to 450-500℃ at a cooling rate of 25-35℃ / h, and finally, the temperature is slowly cooled to room temperature with the bell-type annealing on. This invention employs a two-stage moderate heating and moderate holding control strategy to maintain the annealing temperature within the range of 700~720℃. This avoids the re-dissolution of V(C,N) precipitates while preserving the precipitation strengthening effect formed during the hot rolling coiling stage. The holding time is shortened to 6~8h, utilizing the weak recrystallization inhibition of V to achieve fine grain strengthening. The moderate heating rate (50~70℃ / h) ensures the full development of γ texture (r value ≥2.9) while significantly shortening the annealing cycle and reducing energy consumption. Simultaneously, this process, together with the hot rolling medium-temperature coiling (690~720℃), forms a continuous heat treatment window of coiling-annealing, allowing the V(C,N) precipitates to slightly coarsen during annealing while still maintaining the strengthening effect.
[0045] In one specific embodiment, the slow cooling rate is ≤20°C / h.
[0046] S6. In the finishing process, a leveling mill is used for finishing, with a finishing elongation of 0.6%~1.0% and a roll surface roughness Ra controlled at 2.5~3.5μm. The finishing process adopts a constant elongation control mode to ensure uniform deformation along the length and width of the strip, completely eliminate the yield plateau and ensure the strip shape, and finally obtain excellent surface quality and strip shape.
[0047] The following are specific embodiments. Examples 1-6 The preparation method of 160MPa grade high formability economical IF steel in this embodiment includes smelting, continuous casting, hot rolling, pickling, cold rolling, degreasing, bell-type annealing, and finishing; the preparation method includes the following steps: S1. In the smelting process, this includes hot metal pretreatment, top and bottom blowing converter, LF refining, and RH vacuum refining.
[0048] S2. In continuous casting, a combination of technologies including full-process protective casting, low superheat, electromagnetic stirring, and dynamic light pressure is adopted to ensure the acquisition of high-purity, defect-free billets.
[0049] S3. In hot rolling, the process route of medium-temperature heating + austenitic zone rolling + medium-temperature coiling is adopted.
[0050] In S4, pickling and cold rolling, a combined pickling and rolling unit is used for continuous production. Hydrochloric acid pickling removes the iron oxide scale from the surface of the hot-rolled coil. The cold rolling process uses a hydraulic AGC thickness control system to ensure thickness accuracy and is equipped with bending rolls and shifting roll devices to control the shape of the sheet.
[0051] In S5, the bell-type annealing process uses a full hydrogen protective atmosphere and a two-stage control route of moderate heating and moderate holding.
[0052] S6. In the finishing process, a leveling mill is used for finishing. The finishing process adopts a constant elongation control mode to ensure uniform deformation along the length and width of the strip, completely eliminate the yield plateau and ensure the strip shape, and finally obtain excellent surface quality and strip shape.
[0053] The chemical composition of Examples 1-6 is shown in Table 1, the proportion control of key elements in Examples 1-6 is shown in Table 2, the hot rolling process parameters of Examples 1-6 are shown in Table 3, the cold rolling process parameters of Examples 1-6 are shown in Table 4, and the mechanical property test results of Examples 1-6 are shown in Table 5.
[0054] Table 1 Chemical composition of steel in the examples (wt, %)
[0055] Table 2 Key Element Proportion Control
[0056] Table 3 Main hot rolling process parameters of the steel in the examples
[0057] Table 4 Main cold rolling process parameters of the steel in the examples
[0058] Table 5 Main mechanical properties of the steel in the examples
[0059] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A 160MPa grade high formability economical IF steel, characterized in that, Includes the following components by weight percentage: C≤0.0020%, Si≤0.010%, Mn: 0.08%~0.12%, P: 0.012%~0.020%, S≤0.006%, Als: 0.020%~0.040%, Ti: 0.035%~0.055%, V: 0.008%~0.014%, B: 0.0004%~0.0008%, Ca: 0.001%~0.003%, N≤0.0025%, balance being Fe and unavoidable impurities.
2. The 160MPa grade high formability economical IF steel according to claim 1, characterized in that, The mass percentage ratio of C, Ti and N in the IF steel conforms to the following: Ti / (C+N)=12~18; The chemical composition mass percentage ratio of V and Ti in the IF steel conforms to: V / Ti = 0.15~0.35; The mass percentage ratio of Ca and S in the IF steel conforms to the following: Ca / S = 0.5~2.0; The chemical composition mass percentage ratio of Als and N in the IF steel conforms to: Als / N = 15~20.
3. The 160MPa grade high formability economical IF steel according to claim 1, characterized in that, The IF steel has a yield strength of 145~170MPa; a tensile strength of 305~335MPa; a plastic strain ratio r value ≥2.9; and an elongation A. 80 The percentage is 47% to 51%; the work hardening index (n) is 0.24 to 0.
28.
4. A method for preparing 160MPa grade high formability economical IF steel as described in any one of claims 1-3, characterized in that, The preparation method includes smelting, continuous casting, hot rolling, pickling, cold rolling, degreasing, annealing in a bell, and finishing; the preparation method includes the following steps: In the hot rolling process, the slab is directly fed into a walking beam furnace for heating. The slab heating temperature is 1160~1180℃; the holding time is ≥160min; the roughing rolling temperature is 1060~1100℃, and the cumulative reduction rate is 70%~85%; the finishing rolling temperature is 900~930℃; the finishing rolling cumulative reduction rate is 85%~95%; laminar flow cooling is used after rolling, with a cooling rate of 30~50℃ / s; and the coiling temperature is 690~720℃. In the hood-type annealing, a full hydrogen protective atmosphere is used, and the temperature is raised to 400-500℃ at a heating rate of 200-300℃ / h, then raised to 650-670℃ at a heating rate of 50-70℃ / h, then raised to 700-720℃ at a heating rate of 30-40℃ / h, and held at this temperature range for 6-8h. After that, the temperature is slowly cooled to 450-500℃ at a cooling rate of 25-35℃ / h, and finally slowly cooled to room temperature with the hood on.
5. The method for preparing 160MPa grade high formability economical IF steel according to claim 4, characterized in that, The smelting process includes hot metal pretreatment, top and bottom blowing converter, LF refining, and RH vacuum refining. In the aforementioned molten iron pretreatment, the molten iron undergoes desiliconization, desulfurization, and dephosphorization treatments. In the top-and-bottom combined blowing converter, the final carbon content is controlled to be ≤0.025%, and the final oxygen content is 400~500ppm. During the tapping process, aluminum particles are added for pre-deoxidation, and the slag discharge is controlled by the sliding plate slag-blocking technology, with the slag thickness controlled to be ≤40mm and the slag discharge amount controlled to be ≤60mm. The tapping temperature is controlled to be 1660~1680℃. In the LF refining process, high-basicity reducing slag is used for deep desulfurization, with S ≤ 0.006% and refining time of 35-45 min; the molten steel temperature is controlled at 1610-1630℃; and the CaO / SiO2 ratio of the high-basicity reducing slag is ≥ 5. In the RH vacuum refining process, oxygen blowing decarburization is carried out under a vacuum degree ≤60Pa, and C≤0.0020% and [O]≤0.0025% are controlled. Then alloying is carried out. At the end of the alloying process, Fe-Ca wire is added for calcium treatment, and the calcium treatment is followed by circulation for 3~5 minutes.
6. The method for preparing 160MPa grade high formability economical IF steel according to claim 4, characterized in that, In the continuous casting process, the tundish adopts a low-carbon working layer design with a capacity of ≥60 tons. Argon gas is used for full-process sealing protection from the ladle to the tundish and from the tundish to the crystallizer. The casting superheat is 20~30℃. A combination of electromagnetic stirring in the crystallizer and electromagnetic stirring at the end is used. A dynamic light pressure of 2~5mm is applied at the end of the solidification of the billet. A special protective slag for ultra-low carbon steel is used in conjunction with a weak cooling secondary cooling system. The casting speed is 1.0~1.2m / min to obtain the billet.
7. The method for preparing 160MPa grade high formability economical IF steel according to claim 6, characterized in that, The non-metallic inclusions of types A, B, C, and D in the billet are ≤1.0 grade; the inclusions in the billet are spherical and uniformly distributed; the thickness of the billet is 210~230mm.
8. The method for preparing 160MPa grade high formability economical IF steel according to claim 4, characterized in that, In the pickling and cold rolling processes, a combined pickling and rolling unit is used for continuous production. The iron oxide scale on the surface of the hot-rolled coil is removed by pickling with hydrochloric acid. The total reduction rate of cold rolling is 80% to 90%.
9. The method for preparing 160MPa grade high formability economical IF steel according to claim 4, characterized in that, In the finishing process, a leveling mill is used for finishing, the finishing elongation is 0.6%~1.0%, the surface roughness Ra of the rolls is controlled at 2.5~3.5μm, and the finishing process adopts a constant elongation control mode.
Citation Information
Patent Citations
B microalloying high-elongation low-yield-strength IF steel and manufacturing method thereof
CN113802062A
Method for achieving IF steel ferrite rolling through ultra-short process and near net shape
CN115478143A
High-strength IF steel hot-dip galvanized steel plate and preparation method thereof
CN117551938A
IF steel with yield strength of 180 MPa grade and high yield ratio and production method of IF steel
CN118147537A
Ultra-deep drawing IF steel and preparation method thereof
CN118703877A